The Summit process and collective security : future responsibility sharing : a study group report - Group of Thirty (Washington, DC : Group of Thirty, 1991)
The paper reviews the sharing of responsibility for global security among the major industrial nations, considers the implications for the Summit process and makes some practical recommendations on strengthening the current system
osc 31/01/2019
Loans
Keywords: Summit meetings; World politics; Security, International